Correlation of Mammographic Calcifications with HER-2/neu Overexpression in Primary Breast Carcinomas - Wang, X. (Springer-Verlag, 2008)
HER-2/neu is a valuable therapeutic and prognostic marker in primary breast carcinomas. The aim of this study was to evaluate the association between mammographic calcifications and HER-2/neu overexpression in primary breast carcinomas and assess its clinical perspective. A retrospective study of 152 preoperative mammograms in patients with breast carcinoma was performed. Expression of HER-2/neu was determined by immunohistochemical staining on 152 tissues that comprised specimens of 11 ductal carcinoma in situ (DCIS) and 141 primary invasive carcinomas. Mammographic calcifications were evaluated according to the Breast Imaging Reporting and Data System (BI-RADS), fourth edition. Calcifications were found in 73 (48.0%) out of 152 patients by mammography finding. Calcifications were more common in carcinomas with HER-2/neu overexpression (45:73, 61.6%) than in those without HER-2/neu overexpression (28:79, 35.4%; P = 0.001). Of the 73 carcinomas with calcifications on mammography, mass with spiculated margin as an associated finding of calcifications was more significantly frequent in carcinomas with HER-2/neu overexpression (15 of 45, 33.3%) than in those without HER-2/neu overexpression (2 of 28, 7.1%; P = 0.036). Fine linear morphology was more common in carcinomas with HER-2/neu overexpression (15:45, 33.3%) when compared with those without HER-2/neu overexpression (2:28, 7.1%; P = 0.036). Clustered distribution of calcifications was more common in carcinomas with HER-2/neu overexpression (26:45, 57.8%) compared with carcinomas without HER-2/neu overexpression (6:28, 21.4%; P = 0.048). Mammographic calcifications are correlated with HER-2/neu overexpression in primary breast carcinomas. Calcifications detected during screening mammography are not only of diagnostic value but of use in determining therapeutic options and prognosis.